Contribuição ao projeto de reservatórios cilíndricos de concreto armado apoiados em base deformável - Silva , Rafael Leandro Costa (2017)
Many water supply tanks or storage of other liquids in industries are designed directly supported on foundation ground. Considering the foundation soil is a deformable material on loading, effects of soil-structure interaction are, generally, important and therefore should be considered in the structural design of such tanks. This work proposes to study the effects of deformability of the foundation soil on the stresses and displacements of tanks on ground surface. The structure of the tank in question consists of a cylindrical shell wall, circular bottom plate, roof in the shape of a revolution dome, and rigid ring in the connection between the shells. The soil is admitted as a linear elastic material represented by continuously distributed springs (Winkler’s Model). The analysis procedures are based on the shell theories (membrane and flexion) and thin plate theory and the analysis of the global structure is done through the Force Method. The influence of soil deformability on the stresses and displacements in the structure will be studied through parametric analyses involving soil stiffness and parameters related to the tank geometry. In addition to the structural analysis, which is carried out through a computer code prepared by the author, the work also covers a study on design guidelines for tanks based on recommendations and prescriptions available in the literature, as well as national and international codes. The results show significant differences in the tests considering the deformability of the soil, including, it may occur inversion of the signal of bending moments in the wall and in the bottom slab. Thus, it’s concluded that soil stiffness has a direct influence on the stresses and displacements of the tanks on ground surface.